PENINGKATAN KETERAMPILAN MENULIS TEKS PROSEDUR BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN BERBASIS PROYEK PADA SISWA KELAS X SMA - Asih Rosnaningsih; Devina Aisya Putri; Marisa Heryanti Ilyas; Mutiara Sintya; Ruhimah Ruhimah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2026)
This study aimed to improve students’ English procedure text writing skills through the implementation of the Project-Based Learning (PjBL) model in Grade X students of SMAN 1 Waringinkurung. The background of this study was the students’ low ability in writing procedure texts, particularly in terms of text structure, the use of imperative vocabulary, and the organization of steps in a coherent sequence. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 36 students of class X.1. Data were collected through observation and a procedure text writing test. The data were analyzed descriptively by comparing the results of Cycle I and Cycle II based on the predetermined success indicators. The results showed a significant improvement in students’ writing skills. The percentage of students achieving the minimum mastery criterion increased from 50% in Cycle I to 83.33% in Cycle II. In addition, students’ learning interest and classroom participation also improved and exceeded the success indicators. Therefore, it can be concluded that the implementation of Project-Based Learning is effective in improving students’ English procedure text writing skills at the senior high school level.